Measurement of the production of (anti)nuclei in p–Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; et al. (Physics letters, 2023)
Measurements of (anti)proton, (anti)deuteron, and (anti)3He production in the rapidity range −1<y<0 as a function of the transverse momentum and event multiplicity in p-Pb collisions at a center-of-mass energy per nucleon-nucleon pair sNN=8.16TeV are presented. The coalescence parameters B2 and B3, measured as a function of the transverse momentum per nucleon and of the mean charged-particle multiplicity density, confirm a smooth evolution from low to high multiplicity across different collision systems and energies. The ratios between (anti)deuteron and (anti)3He yields and those of (anti)protons are also reported as a function of the mean charged-particle multiplicity density. A comparison with the predictions of the statistical hadronization and coalescence models for different collision systems and center-of-mass energies favors the coalescence description for the deuteron-to-proton yield ratio with respect to the canonical statistical model.